{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

MIT18_02SC_pb_30_comb

# MIT18_02SC_pb_30_comb - Chain rule and total dierentials 1...

This preview shows pages 1–2. Sign up to view the full content.

Chain rule and total differentials the total 1 . Find differential of w = z e ( x + y ) at (0 , 0 , 1). Answer: The total differential at the point ( x 0 , y 0 , z 0 ) is dw = w x ( x 0 , y 0 , z 0 ) dx + w y ( x 0 , y 0 , z 0 ) dy + w z ( x 0 , y 0 , z 0 ) dz. In our case, w = ( x + y ) = z e ( x + y ) x z e , w y , w z = e ( x + y ) Substituting in the point (0 , 0 , 1) we get: w x (0 , 0 , 1) = 1 , w y (0 , 0 , 1) = 1 , w z (0 , 0 , 1) = 1 . Thus, dw = dx + dy + dz. 2 . dw Suppose w = z e ( x + y ) and x = t , y = t 2 , z = t 3 . Compute and evaluate it when dt t = 2. Answer: We use the chain rule: dw ∂w dx ∂w dy ∂w dz = + + dt ∂x dt ∂y dt ∂z dt = ( z e ( x + y ) )(1) + ( z e ( x + y ) )(2 t ) + (e ( x + y ) )(3 t 2 ) . At t = 2 we have x = 2 , y = 4 , z = 8 . Thus, dw

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}